2021
DOI: 10.3758/s13421-020-01129-y
|View full text |Cite
|
Sign up to set email alerts
|

Can you believe it? An investigation into the impact of retraction source credibility on the continued influence effect

Abstract: The continued influence effect refers to the finding that people often continue to rely on misinformation in their reasoning even if the information has been retracted. The present study aimed to investigate the extent to which the effectiveness of a retraction is determined by its credibility. In particular, we aimed to scrutinize previous findings suggesting that perceived trustworthiness but not perceived expertise of the retraction source determines a retraction's effectiveness, and that continued influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 87 publications
7
69
7
Order By: Relevance
“…Further, research could examine additional factors that impact the amount of discomfort felt in response to a retraction. One possibility is that retractions from more versus less credible sources might be seen as a greater challenge to one's causal understanding of an event (Ecker & Antonio, 2021;Guillory & Geraci, 2013), making such retractions especially uncomfortable to encounter. Additionally, in some cases the amount of discomfort felt in response to a retraction might be impacted by considerations of how accepting or rejecting the retraction might impact one's relationship with the person or entity issuing the retraction (Scoboria & Henkel, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, research could examine additional factors that impact the amount of discomfort felt in response to a retraction. One possibility is that retractions from more versus less credible sources might be seen as a greater challenge to one's causal understanding of an event (Ecker & Antonio, 2021;Guillory & Geraci, 2013), making such retractions especially uncomfortable to encounter. Additionally, in some cases the amount of discomfort felt in response to a retraction might be impacted by considerations of how accepting or rejecting the retraction might impact one's relationship with the person or entity issuing the retraction (Scoboria & Henkel, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the previously discussed theoretical contributions, this research adds additional granularity to the measurement of psychological mechanisms that might play a role in the CIE. To date, CIE research has largely been divided on the main outcome of interest. Much research has focused on how retractions impact the extent to which participants continue to make inferences about the focal event based on the misinformation (e.g., Ecker & Ang, 2019;Ecker & Antonio, 2021;Ecker, Lewandowsky & Apai, 2011;Ecker et al, 2015;Ecker et al, 2014;Ecker, Lewandowsky, et al, 2011;Ecker et al, 2010;Johnson & Seifert, 1994;Rich & Zaragoza, 2016;Wilkes & Leatherbarrow, 1988). Other research has focused on how retractions impact continued belief that the misinformation is true (e.g., Nyhan & Reifler, 2010;Nyhan et al, 2014;Nyhan et al, 2013;Schwarz et al, 2007;Skurnik et al, 2005;Swire, et al, 2017), though some of this research has measured both outcomes.…”
Section: Differentiating Belief In Misinformation From Use Of Misinformation To Make Inferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…One form of intervention designed to combat misinformation focuses on providing source information to viewers. Across a number of studies, manipulating source trustworthiness was more impactful than knowledge of source credibility (i.e., Ecker & Antonio, 2021;Pluviano & Della Sala, 2020). In some cases, emphasizing publisher information had little to no effect on accuracy ratings (Dias et al, 2020;Wintersieck et al, 2018).…”
Section: Key Takeawaysmentioning
confidence: 99%
“…Based on this research, several best-practice recommendations have been identified. Specifically, refutations should: (a) come from a trustworthy source (Ecker & Antonio, 2020;Guillory & Geraci, 2013) and, if applicable, discredit the disinformant by exposing their hidden agenda (Walter & Tukachinsky, 2020); (b) make salient the discrepancy between false and factual information, which has been shown to facilitate knowledge revision (Ecker, Hogan, & Lewandowsky, 2017;Kendeou, Butterfuss, Kim, & van Boekel, 2019); (c) explain why the misinformation is false, providing factual information to replace the false information in people's mental models (Paynter et al, 2019;Swire et al, 2017); and (d) draw attention towards any misleading strategies employed by misinformants (Cook et al, 2018;MacFarlane, Hurlstone, & Ecker, 2018, 2020a.…”
Section: Refuting Spurious Covid-19 Treatment Claims Reduces Demand and Misinformationmentioning
confidence: 99%